Derivation of ionization equations for the simulation of auroral effects - CITRYNELL, HAROLD (MAUSAM, 1975)
Equations are derived for calculating ionization rates for three basic types of electron energy spectrum distributions. These can be combined to model observed auroral electron energy distributions, in order to simulate auroral effects and effects due to electron precipitation, Calculated auroral 5577 A0/3914 A0 intensity ratios, using the ionization rates obtained by means of the derived equations, at the altitudes of 120, 160 and 200 km, show good agreement with observations.